The food of Japan authentic recipes from the land of the rising sun - Hulton, Wendy (Singapore Periplus Editions (HK) Ltd., 1999)
A collection of recipes ranging from simple noodle dishes to elegant and exotic presentations - Also introduces the reader to cultural attitudes that have helped shape the cuisine - Japanese kitchen
Includes index.
Keywords: Cooking, Japanese